2012
DOI: 10.1111/j.1365-2672.2012.05349.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial succession during curing process of a skate (Dipturus batis) and isolation of novel strains

Abstract: Aims: To study the succession of cultivated and uncultivated microbes during the traditional curing process of skate. Methods and Results: The microbial diversity was evaluated by sequencing 16Sr RNA clone libraries and cultivation in variety of media from skate samples taken periodically during a 9-day curing process. A pH shift was observed (pH 6·64-9·27) with increasing trimethylamine (2·6 up to 75·6 mg N per 100 g) and total volatile nitrogen (TVN) (from 58·5 to 705·8 mg N per 100 g) but with relatively sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our results are consistent with a role for TAAR5 in aversion to TMA in humans. Carriers of the TAAR5 variant rated the fish odor as less unpleasant and were less likely to describe it as fermented skate or shark, which contain high levels of TMA [33,35] and are generally considered to have a very foul odor. In contrast, carriers were more likely to use non-seafood-related descriptors with neutral or positive odor valence.…”
Section: Article Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with a role for TAAR5 in aversion to TMA in humans. Carriers of the TAAR5 variant rated the fish odor as less unpleasant and were less likely to describe it as fermented skate or shark, which contain high levels of TMA [33,35] and are generally considered to have a very foul odor. In contrast, carriers were more likely to use non-seafood-related descriptors with neutral or positive odor valence.…”
Section: Article Discussionmentioning
confidence: 99%
“…The lead missense variant at the locus is presented. S6) showed that carriers were less likely to use fermented fish descriptors such as ''fermented skate'' and ''shark'' (p = 4.1 3 10 À4 , OR = 0.51, 95% CI = 0.35, 0.74), which contain high levels of TMA and have a foul odor due to ammonia and TMA produced during fermentation [33][34][35]. Carriers were more likely to use descriptors that are generally not considered foul-smelling (i.e., have neutral or positive odor valence) and are not seafood-related, such as ''potatoes,'' ''ketchup,'' ''caramel,'' and ''rose'' (p = 3.1 3 10 À8 , OR = 2.17, 95% CI = 1.65, 2.85).…”
Section: Confirmation Of Associations With Olfactory Measures In Replication Samplementioning
confidence: 99%
“…Compared to LAB, there are few studies reporting Gammaproteobacteria to be dominating in fermented food. This taxon has been found dominant in shellfish [18] and in cured skate [41]. However, several studies found Gammaproteobacteria as a non-dominant part of the bacteria in fermented food [42,43,44] or found that the domination of this taxon has been replaced by Firmicutes towards the end of the fermentation [15,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…While a much higher ammonia nitrogen content in fermented skate samples was observed than that of fresh skates. According to Reynisson et al [20] and Cho et al, [25] Genus Pseudomonas and Thiopseudomonas were a predominant bacterium in fermented skate sample. And those two genera have been reported that predominantly produces alkaline proteolytic enzymes, which catalyze the cleavage of peptide bonds in meat proteins.…”
Section: Analysis Of Ph and Ammonia Nitrogen Contentmentioning
confidence: 93%
“…[19] Unlike other fish species, skate retains high urea and trimethylamine N-oxide (TMAO) in their muscle tissue as organic osmolytes at relatively high concentrations urea at 292-369 mmol/kg wet mass and TMAO at 85-168 mmol/kg wet mass, which leads to a significant increase in pH values and formation of unique ammonia flavors by the action of microorganisms during the fermentation. [7] A bacterial succession during the curing process of a skate has been investigated by Reynisson et al [20] that the key players in skate samples during fermentation are organisms belonging to Oceanisphaera, Psychrobacter, Pseudoalteromonas genera and some species within the Pseudomonas genus. Both Oceanisphaera and Pseudoalteromonas had a strong urease activity and were present in high relative quantity in the beginning of the fermentation.…”
Section: Analysis Of Ph and Ammonia Nitrogen Contentmentioning
confidence: 99%